2008
DOI: 10.1093/humrep/den132
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy chances on an IVF/ICSI waiting list: a national prospective cohort study

Abstract: The chance of an ongoing pregnancy without treatment while waiting for an IVF or ICSI is below 10% but may be as high as 25% within 1 year for selected patient groups. Timing of IVF should take predictive factors into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
43
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 18 publications
10
43
1
4
Order By: Relevance
“…However, the proportion of women with colorectal involvement in this study was not clearly identified in the initial report. This spontaneous PR is in agreement with those of previous studies, not focusing on a population with colorectal endometriosis, reporting a spontaneous PR of about 10% [22,31].…”
Section: Spontaneous Fertility In Women With In Situ Colorectal Endomsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the proportion of women with colorectal involvement in this study was not clearly identified in the initial report. This spontaneous PR is in agreement with those of previous studies, not focusing on a population with colorectal endometriosis, reporting a spontaneous PR of about 10% [22,31].…”
Section: Spontaneous Fertility In Women With In Situ Colorectal Endomsupporting
confidence: 93%
“…In addition to a previous meta-analysis demonstrating the low spontaneous PR especially in women with advanced stages of the disease [21], Eijkemans et al evaluated the chance of pregnancy on an IVF-ICSI waiting-list of couples with various causes of infertility [22]. They found that the cumulative probability of treatment-free ongoing pregnancy was 9% at 12 months.…”
Section: Issues On Fertility and Colorectal Endometriosismentioning
confidence: 99%
“…An observational study of 1236 couples with UI in the Netherlands noted that between 10 and 25 % conceived during 1 year while being on a waiting list to undergo IVF [13]. Overall, approximately 1 to 4 % of couples with UI will conceive spontaneously each month.…”
Section: Treatment Of Unexplained Infertilitymentioning
confidence: 99%
“…Açıklanamayan infertilite teşhisi konmuş çiftler üzerinden yapılmış kapsamlı bir çok araştırmada, spontan gebe kalma oranı oldukça yüksek bulunmuştur (3,4,7). Hollanda'da IVF tedavisi için bekleyen çiftleri kapsayan çalışmanın sonuçları, 1 senedir bekleyen çiftlerde gebe kalma oranını %13 olarak bulmuştur (7).…”
Section: Açıklanamayan Infertilitenin Bekleyerek (Ekspektan) Tedavisiunclassified
“…Hollanda'da IVF tedavisi için bekleyen çiftleri kapsayan çalışmanın sonuçları, 1 senedir bekleyen çiftlerde gebe kalma oranını %13 olarak bulmuştur (7). Açıklanamayan infertilitesi olan çiftlerin yaklaşık %1-4'ü her ay spontan olarak gebe kalabilmektedir.…”
Section: Açıklanamayan Infertilitenin Bekleyerek (Ekspektan) Tedavisiunclassified